Patient Experiences and Opinions of a Behavioral Activation Group Intervention for Depression. (January 2019) - O'Neill, Laura; Samaan, Zainab; McCabe, Kathleen; Tabak, Terri Ann; Key, Brenda; Litke, Kathryn; Whattam, Jeff; Garrick, Laura; Chalmers, Sandra; Xie, Feng; Thabane, Lehana; Patel, Yogita; et al.
Purpose: Major depressive disorder is the leading cause of disability worldwide. This study is part of a mixed methods pilot trial, exploring the effectiveness, acceptability, and feasibility of providing behavioral activation (BA) treatment in a group format. Methods: Using an applied, descriptive approach, qualitative data were collected from individual interviews (18) and focus groups (5) at multiple data points throughout the trial and feedback given to group facilitators, who adapted the program accordingly. Results: Group BA is an effective and acceptable treatment format when a client-centered, flexible approach is utilized. This contrasted with findings from the comparison intervention, a peer support group, from which participants reported no benefit. Conclusions: Group BA is beneficial in a fiscally responsible evidenced-based health-care culture. Comparator groups need to be carefully selected. Engaging patient and clinician perspectives when designing and implementing new clinical interventions is vital in informing future research and social work practice.